FINANCIAL ANALYSIS WITH PROFIT AND LOSS APPROACH IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) BUAH BUK NUR - Sindi Oktapia; Juli Meliza (Jurnal Ekonomi, 2023)
This study is entitled "Financial Analysis with a Profit and Loss approach in Small and Medium Enterprises (MSMEs) Buah BUk Nur" with the aim to find out the financial performance of Buah Buk Nur MSMEs based on the Profit and Loss approach. While the research method used in this study is a descriptive method of financial finance and will later record the financial condition of Buah Buk Nur MSMEs. This study concluded that the financial performance of these MSMEs during the six-month period experienced instability due to the lack of optimal planning in their activities so that they were not in accordance with the planned target